De novo Cancer‐Related Death in Australian Liver and Cardiothoracic Transplant Recipients. Issue 5 (6th March 2013) - Na, R.; Grulich, A. E.; Meagher, N. S.; McCaughan, G. W.; Keogh, A. M.; Vajdic, C. M.
<x xml:space="preserve">Abstract</x> Evidence is sparse on the relative mortality risk posed by de novo cancers in liver and cardiothoracic transplant recipients. A retrospective cohort study was conducted in Australia using population‐based liver (n = 1926) and cardiothoracic (n = 2718) registries (1984–2006). Standardized mortality ratios (SMRs) were computed by cancer type, transplanted organ, recipient age and sex. During a median 5‐year follow‐up, de novo cancer‐related mortality risk in liver and cardiothoracic recipients was significantly elevated compared to the matched general population (n = 171; SMR = 2.83; 95% confidence interval [95%CI], 2.43–3.27). Excess risk was observed regardless of transplanted organ, recipient age group or sex. Non‐Hodgkin lymphoma was the most common cancer‐related death (n = 38; SMR = 16.6; 95%CI, 11.87–22.8). The highest relative risk was for nonmelanocytic skin cancer (n = 23; SMR = 49.6, 95%CI, 31.5–74.5), predominantly in males and in recipients of heart and lung transplants. Risk of death from de novo cancer was high in pediatric recipients (n = 5; SMR = 41.3; 95%CI, 13.4–96.5), four of the five deaths were non‐Hodgkin lymphoma. De novo cancer was a leading cause of late death, particularly in heart and liver transplantation. These findings support tailored cancer prevention strategies, surveillance to promote early detection, and guidelines for managing immunosuppression once cancer occurs.